Perdão interpessoal e ansiedade em mães de autistas por injustiças percebidas contra seus(suas) filhos(as) - Soulat, Anna Mayra Teófilo (2025)
The aim of this thesis was to investigate the relationship between interpersonal forgiveness and anxiety in mothers of autistic children and mothers of typical children due to perceived injustices against their children. To this end, a mixed-method, with a quantitative and qualitative approach, it was used to explore and compare interpersonal forgiveness and maternal anxiety in mothers of children with autism spectrum disorder and mothers of neurotypical children. Data were obtained using the Enright Forgiveness Scale-30 (Enright et al., 2022), the State Anxiety Inventory (Spielberger et al; 1979, validated in Portuguese by Biaggio & Natalício, 2003), the Social Desirability Scale (Crowne & Marlowe, 1960; Gouveia et al., 2009) and, in addition to these instruments already consolidated internationally, an instrument was also constructed involving the analysis of sociodemographic data. The thesis was divided into two phases, the bibliographical and the empirical. The first part, bibliographical, presented three bibliographical reviews, namely: (1) Vicissitudes of neuroatypical mothering: on autism and the injustices, discrimination, and social exclusions of autistic mothering; (2) Mental health and anxiety in atypical mothering (ASD); and (3) Definition, theory, and clinical studies of interpersonal forgiveness. For the second, empirical part, the research sample included 96 mothers, leaving 86, namely, 42 mothers of children with ASD and 44 mothers of neurotypical children. These mothers were divided into two groups, based on the data obtained in the screening, Group of ASD mothers (G1) and Group of NTPS mothers (G2). Group 1 (ASD mothers), when compared to group 2 (NTPS mothers), not only presented a different context and frequency of interpersonal forgiveness, but also presented a greater perception of hurt, a lower degree of forgiveness, and a negative impact on state and especially trait anxiety, probably due to a greater number of injustices experienced by their type of mothering. Thus, the research elucidated the importance of interpersonal forgiveness as a potential coping mechanism for maternal anxiety (ASD) and suggested focusing on anxiety in ASD mothers as a reality related to the stigma and social exclusion experienced by these mothers. The implications of the results involving interpersonal forgiveness and anxiety in mothers (ASD) and mothers (NTPS) are presented in the discussion. The study presented as a gap the lack of control over the age of mothers and age/sex of children and the non-applicability/development of forgiveness psychotherapy in mothers with a high level of hurt/anger and with a high level of anxiety, especially trait anxiety. Thus, since this study demonstrates the relationship between injustice, hurt, forgiveness and anxiety, future studies should be conducted to verify the impact of forgiveness psychotherapy in reducing anxiety disorders in mothers (ASD).